Heat transfer enhancement in microchannel systems through geometric modification of vortex generators and nanofluid integration: A numerical study - Chuan-Chieh Liao; Wen-Ken Li; Hui-En Lin (Results in Engineering)
The numerical study investigates heat transfer enhancement in microchannels using vortex generators (VGs) and nanofluids, employing Buongiorno's two-phase model to accurately capture nanoparticle dynamics. Previous research has largely addressed the effects of thermal efficiency (ΦT) and mechanical penalty (ΦM) separately for various VG configurations. The innovation centers on utilizing the thermal performance factor (TPF) to evaluate the trade-off between improved ΦT and associated ΦM, providing a comprehensive performance analysis. Results indicate that the circular VGs significantly enhance heat transfer through secondary flow and thermal boundary layer disruption, but this improvement comes at the cost of increased flow resistance. Rectangular VGs offer improved performance, with an increase in aspect ratios from 0.5 to 20 reducing ΦM by 76.7 % and improving TPF by 12 %. Incorporating Al₂O₃ nanofluids further optimizes performance; at a nanoparticle concentration of φ = 0.6 %, NuMean increases by 15.7 % with only a 3.4 % rise in pressure drop, achieving a TPF exceeding unity. Beyond φ = 0.6 %, the thermal conductivity gains of nanofluids outweigh viscosity-induced flow resistance. These findings highlight the potential of combining optimized VG geometries and nanofluids to enhance microchannel heat transfer, offering a promising solution for high-density thermal management systems.